Mustafa Kamal Ataturk and the Kurds between The year 1916- 1925 (Journal of the College of Basic Education, 2022)
The events after the First World War resulted in the fall of the Ottoman Empire. The war culminated in the emergence of the Turkish national movement under the leadership of Mustafa Kamal (Ataturk) in the eastern part of present-day Turkey, that is inhabited by a Kurdish majority, far from the Anglo-French occupation areas. Ataturk knew the region, worked in it and understood its geographical and military importance, so he worked to gain the support of the Kurdish tribal leaders for his movement. This was in order to make them work together for it, and to support him militarily, especially after the allies' support for the Kurdish cause weakened, which reflected negatively on the activities of the Kurds themselves. When he held his first conference, he appointed a number of Kurdish leaders without their knowledge, and some of those who participated in the conference believed that Ataturk would grant the Kurds their national rights in the new Turkey. However, the Kurdish political leaders and their intellectuals did not give their support to Ataturk, neither in his wars nor in his conferences. This was based on the calls of the Kurdish national organizations. Even though the Kurds who cooperated with Ataturk formed a minority, he gained public opinion through his media and propaganda and showed the world that the Kurds support his movement and are satisfied with their participation in the Turkish administration.